Strategi dan Kepemimpinan Kiai Dalam Meningkatkan Kualitas Dan Kuantitas Santri di Pondok Pesantren Miftahut Thullab Gedangan - Faddol, Moh.; Salim, Moh. (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2025)
Islamic boarding schools are traditional Islamic educational institutions for studying and practicing Islamic teachings by emphasizing the importance of religious knowledge and morals as guidelines for daily behavior. In Islamic boarding schools there are Kiai as leaders who have an important role in managing Islamic boarding schools, especially coaching in improving the quality and quantity of students. Of course, this is not easy, so there needs to be a strategy that Kiai has to implement to improve the quality and quantity of the students. Based on this, there are three problems that are the focus of discussion in this research, namely First, What is the Kiai’s Strategy for Improving the Quality and Quantity of Santri at the Miftahut Thullab Gedangan Islamic Boarding School? Second, what is the quality of the students at the Miftahut Thullab Gedangan Islamic Boarding School? Third, what is the quantity of students at the Miftahut Thullab Gedangan Islamic Boarding School?. The results of the research conducted show that: First, there are several strategies used by Kyai to improve the quality of santri, namely the strategy for dividing leadership tasks, the strategy for empowering asatid, the strategy for preparing programs for santri and the strategy for involving kiai in every activity. The Kiai’s strategies for increasing the quantity of santri are: Strategy for creating a forum for santri guardians, strategy for distributing santri, strategy for widening the wings of Islamic boarding schools in each village, strategy for social media and print media and collaboration strategy for book and general lessons. Second, there are several qualities of students that researchers found, namely, Intellectual Quality, Spiritual Quality, Quality of Skills and Knowledge obtained in accordance with Community Needs. Third, the strategy carried out by the Gedangan Islamic Boarding School Kiai affects the quantity of students from year to year, initially there were only a few students, after this strategy the quantity of students increased, because every year it increased by 80-90, while the number of students now in 2023 is the same as The researchers’ findings amounted to 695 students.